Effects of competition and its outcome on serum testosterone, cortisol and prolactin - Suay, F.; Salvador, A.; Gonzalez-Bono, E.; Sanchis, C.; Martinez, M.; Martinez-Sanchis, S.; Simon, V. M.; Montoro, J. B. (1999)
In order to study the hormonal response to the competition, 28 subjects of similar body weight, physical fitness and sports scores have faced each other in the competitive session (COMBAT). All of them reached similar levels of La and HR and similar scores in the subjective scales of effort. Before the competition, the winners showed greater expectations (possibilities and ability to win) than losers. After the fight, the winners were more satisfied with their performance and with the outcome than losers and they considered that their expectations had been fulfilled, that the referee's performance had been right and that the outcome would be the same if the combat took place again. For the hormonal response, the effect of the outcome was significant just on C. Androgenic levels did not show significant differences between winners and losers, in agreement with Elias (1981), who reported differences in the percentage changes experienced by winners and losers but not in hormonal levels. In the winners, T levels rose significantly during the combat as has been previously described (Mazur et al., 1992; Salvador et al., 1993), whilst, among the losers, there was a greater variability (9 increments and 5 decrements), suggesting that the main difference between them could be the androgenic response. Analysing the hormonal response of each group separately, it can be seen that androgenic response of winners is more intense. For winners and also for the total sample, there were significant differences between androgenic levels before and after the fight, which have not been found in the losers' group. It suggests that defeat is probably the most relevant factor affecting the hormonal response to competition. For stress hormones, in both groups, C and PRL levels rose during the competition, as could be expected since fighting must be a stressor for all the contenders. Conversely to other studies (Mazur and Lamb, 1980; Elias, 1981; Booth et al., 1989), our results did not show significant differences between hormonal changes experienced by winners and losers in COMBAT. It must be pointed out that the mentioned studies used non-parametric tests, less conservative than the parametric tests used in our work. Moreover, the differences reported by each one of theese studies were found in different intervals, which do not allow us to consider that the results have been replicated. Since our design included two other sessions, we can compare the hormonal responses of winners and losers in the three sessions. The winners' hormonal response was very similar in COMBAT and ERGOM, whilst losers experienced significantly greater androgenic changes in the non-competitive effort. Compared with the non-competitive non-physical stress experienced in CONTROL, winners showed a more pronounced hormonal response to the competition than losers. Androgenic changes of winners were significantly greater in COMBAT, whilst losers experienced similar androgenic changes in both sessions. Considering the hormonal levels of losers, the main difference between competitive and non-competitive stress is that stress hormone levels are higher in the competition. Since the winners' hormonal response to the competition is similar to the response observed in the non-competitive exercise, the differences observed in losers could be attributed to a negative effect of the experience of being defeated: there are the losers who showed an androgenic response less intense than could be expected attending to the physical effort performed. In previous studies (Salvador et al., 1987, 1990) it has been suggested that the sports category could affect the hormonal response to the competition. If, as has been proposed by Mazur (1985), the outcome of aggressive interactions could produce different hormonal responses which, in their turn, are able to affect the future involvement of individuals in new aggressive encounters, it can be thought that the sports category or status can be a more important difference than merely winning or losing a single combat. In the terms used by Mazur (1983), if the T response is more related to dominant than to strictly aggressive behaviour, hormonal levels would be dependent on the outcome of a fight, only if it contributes to the statement of new dominance-submission relationships. It can be said that, in sports competitions, the hormonal changes would be modulated by the consequences on the sports status or category, which is not always an objective measure since it would depend on the cognitive appraisal of the subject about his-her own situation after the competition. In our competitive event, the subjects did not gain titles or improve their sports category. In spite of that, when we divide the total sample after the sports category of each judoist, only the high category subjects experience significant androgenic increases in the competition. This is a very similar response to the one observed in the winners' group. Conversely, the low category judoists showed an androgenic response more similar to the one observed in losers. There are no differences between sport categories in the other two sessions. It seems to indicate that this variable could just affect the changes produced in competitive situations. It can be interpreted considering the possibility that the high category subjects perceive the combat as a more threatening situation, since defeat could be more aversive for them than for the low category subjects. Nevertheless, comparing winners and losers from both categories, it can be seen that the high category winners did not show different androgenic responses than winners or losers of low category. Only when considering stress hormones there are some significant differences. The low category losers showed higher post-combat PRL levels, and the high category losers showed higher pre-combat PRL levels than the low category winners. So, we should not state that the sports category, at least in this study, can significantly affect his hormonal response to the competition. It is possible that the differences in sports category among the subjects of our sample were not high enough as to elicit different hormonal responses. The judoists had been matched as to ensure that the fights would be equilibrated, which can reduce the differences in sports category. To study the influence of some cognitive variables on the hormonal response, the scores obtained in the Expectations Items have been correlated with hormonal levels and percentage changes. There was a relationship between androgens and interest in winning. Pre-combat levels were negatively correlated with this item in the total sample and in the winners' group, whilst percentage changes were positively correlated in all groups. For the stress hormones, there is a positive correlation between C levels and self-attributed possibilities and ability to win. The pattern of correlation was very similar in the winners' group. Among losers, the interest to win was positively correlated with androgenic changes. Although in the losers' group there were only four significant correlation values (whilst there were 12 in the total sample and 13 in the winners' group), it can not be stated that this fact constituted an important difference. Analysing the relationships between the Outcome Valuation Items and the hormones studied, there are clearly different correlation patterns in winners and losers. In winners, there are more significant values (17) than in losers (only 6). It must be noted that satisfaction with the outcome negatively correlates with T levels and C changes. Also, the subjects who considered that they could have performed better showed lower C levels. Conversely, in the losers' group, the subjects who considered that their expectations had not been fulfilled, experienced lower T, C and FAI changes. It seems to suggest that the expectations about their own performance, and the cognitive valuation of the outcome are able to influence the hormonal response to the competition, as has been proposed by Mazur et al. (1980, 1992). For C, the winners who viewed themselves as having more possibilities and ability to win, also had higher previous levels and, probably as a consequence of that, experienced less changes. This is not true for losers. The losers who considered to have more possibilities to win, had higher levels and experienced greater C changes. It could be interpreted as if the frustration derived from the defeat was able to elicit a higher anxiety in this subjects than in the judoists who did not view themselves as being able to win. For PRL, the winners who considered the combat as equilibrated showed higher post-combat levels, whilst the judoists who self-attributed less ability to win, experienced less changes. So it is possible to conclude that the relationships between the psychological state variables and the hormones are modulated not only by the outcome but also by the subjects' expectations and valuations, as was suggested by Mazur and Lamb (1980), McCaul et al. (1992) and Mazur et al. (1992). These psychological variables seem to be more important than the `objective` measures of satus, at least, in situations in which sports category differences are not very large.